2018
DOI: 10.1016/j.mineng.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and texture of the Storforshei iron formation, and their effect on grindability

Abstract: Investigating how ore mineralogy and texture affect the recovery from the processing plant is important for any mining operation. The results will assist in production planning and optimising the utilisation of a deposit. Easily available validated tests are desirable and useful.The Storforshei iron formation (IF) consists of several iron oxide deposits with mineralogical and textural differences. Although the Fe grades of the ores are similar, mineralogical and textural characteristics of the deposits affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Unfortunately, often the relation between datasets cannot be explained only by modal mineralogy and bulk chemistry. There are multiple influencing factors such as mineral textures (Lund et al, 2015;Tøgersen et al, 2018) mineral associations and the degree of liberation (Hunt et al, 2011;Johnson et al, 2007;Minz et al, 2013). These properties were not measured in this study, though they should be considered in future geometallurgical investigations due to the impact they might have in characterizing the material and its processability (Lamberg, 2011;Williams, 2013).…”
Section: Data Correlation and Model Confirmationmentioning
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, often the relation between datasets cannot be explained only by modal mineralogy and bulk chemistry. There are multiple influencing factors such as mineral textures (Lund et al, 2015;Tøgersen et al, 2018) mineral associations and the degree of liberation (Hunt et al, 2011;Johnson et al, 2007;Minz et al, 2013). These properties were not measured in this study, though they should be considered in future geometallurgical investigations due to the impact they might have in characterizing the material and its processability (Lamberg, 2011;Williams, 2013).…”
Section: Data Correlation and Model Confirmationmentioning
confidence: 93%
“…However, mineral processing performance indicators can be explained with mineralogical data, unfortunately it often presents additivity issues (Dunham and Vann, 2007;Lishchuk et al, 2019). Examples of mineralogical data explaining processing performance are mineralogical textures and associations (Johnson et al, 2007;Koch et al, 2019;Lund et al, 2015;Mwanga et al, 2015;Pérez-Barnuevo et al, 2018;Tøgersen et al, 2018). Usually, the relation between mineralogical data and mineral processing performance is non-linear relationship, thus a non-linear estimation technique, like an artificial neural network framework, could favourably be used.…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between petrographical and mechanical properties of rocks have been investigated in several studies [2,3,21,22,23,24]. The rock mechanics and crushability tests are frequently used in the simulation and modelling of the processes occurring in the comminution equipment, and they can be used in the studies of the relationship between rock properties and grindability [25].…”
Section: Relationship Between Petrographical Properties and The Crushmentioning
confidence: 99%
“…It reveals the lines between the chemical system and the mineralogical system by partially selecting the important features of each dataset. Several case studies demonstrated the value of mineralogical and textural information through data fusion, for optimisation of process performances such as comminution [6][7][8]. Based on this success, new ML techniques could reveal the links between the data.…”
Section: Introductionmentioning
confidence: 97%